INSTALASI RUNNING TEXT SEBAGAI ALAT BANTU INFORMASI DALAM RANGKA MENARIK MINAT BACA DI DESA JAYASAKTI - Muhammad Alfado; Rabianur Lubis; Adli Azhari (Universitas Islam 45 Bekasi, 2023)
The Real Work Lecture Program (KKN) for installing running text as an information aid in order to attract reading interest in Jayasakti village has been implemented. The aim of this program is to increase the reading interest of the people in Jayasakti village through the use of information aids in the form of running texts. The method used in this program is the observation method in the form of data collection, making running texts, and installing running texts in Jayasakti village. The result of this running text installation program is the creation of an interesting atmosphere for people in Jayasakti village to read the information displayed through running text. In addition, this program has also succeeded in increasing the reading interest of the Jayasakti village community. Thus, this program can be used as an effort to increase interest in reading in other villages.